2024
DOI: 10.3390/metabo14010068
|View full text |Cite
|
Sign up to set email alerts
|

Citrus clementine Peel Essential Oil Ameliorates Potassium Dichromate-Induced Lung Injury: Insights into the PI3K/AKT Pathway

Hany G. Attia,
Suzan M. El-Morshedy,
Ahmed M. Nagy
et al.

Abstract: Acute Lung Injury (ALI) is a life-threatening syndrome that has been identified as a potential complication of COVID-19. There is a critical need to shed light on the underlying mechanistic pathways and explore novel therapeutic strategies. This study aimed to examine the potential therapeutic effects of Citrus clementine essential oil (CCEO) in treating potassium dichromate (PDC)-induced ALI. The chemical profile of CCEO was created through GC–MS analysis. An in vivo study in rats was conducted to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…7 The phosphoinositide 3-kinase (PI3 K)/Akt signaling pathway is linked to the formation of pulmonary fibrosis induced by novel coronavirus pneumonia, and d-limonene can reduce PI3K/protein kinase B (Akt)/IκB kinase-α (IKK-α)/nuclear factor kappa-B (NF-κB) p65 signaling pathway expression and phosphorylation. 8,9 Chi et al 10 found that limonene (20, 50, and 75 mg/kg) had a strong antiinflammatory effect and could significantly improve lung function in mice with lipopolysaccharide-induced acute lung damage, with the mechanism being related to the inhibition of extracellular signal-regulated kinase (ERK), p38 Mitogen-activated protein kinase (MAPK), NF-κB, and C-Jun N-terminal kinase signal pathways. D'Alessio et al 11 found that limonene (10 mg/kg) lowered TNF-α levels and inflammation in colitis model rats.…”
Section: Anti-inflammatory and Analgesic Effectsmentioning
confidence: 99%
“…7 The phosphoinositide 3-kinase (PI3 K)/Akt signaling pathway is linked to the formation of pulmonary fibrosis induced by novel coronavirus pneumonia, and d-limonene can reduce PI3K/protein kinase B (Akt)/IκB kinase-α (IKK-α)/nuclear factor kappa-B (NF-κB) p65 signaling pathway expression and phosphorylation. 8,9 Chi et al 10 found that limonene (20, 50, and 75 mg/kg) had a strong antiinflammatory effect and could significantly improve lung function in mice with lipopolysaccharide-induced acute lung damage, with the mechanism being related to the inhibition of extracellular signal-regulated kinase (ERK), p38 Mitogen-activated protein kinase (MAPK), NF-κB, and C-Jun N-terminal kinase signal pathways. D'Alessio et al 11 found that limonene (10 mg/kg) lowered TNF-α levels and inflammation in colitis model rats.…”
Section: Anti-inflammatory and Analgesic Effectsmentioning
confidence: 99%